Lyophilization induces physicochemical alterations in cryptococcal exopolysaccharide. (1st September 2022) - Wear, Maggie P.; Hargett, Audra A.; Kelly, John E.; McConnell, Scott A.; Crawford, Conor J.; Freedberg, Darón I.; Stark, Ruth E.; Casadevall, Arturo
Abstract: Microbial polysaccharide characterization requires purification that often involves detergent precipitation and lyophilization. Here we examined physicochemical changes following lyophilization of Cryptococcus neoformans exopolysaccharide (EPS) . Solution 1 H Nuclear Magnetic Resonance (NMR) reveals significant anomeric signal attenuation following lyophilization of native EPS while 1 H solid-state Nuclear Magnetic Resonance (ssNMR) shows few changes, suggesting diminished molecular motion and consequent broadening of 1 H NMR polysaccharide resonances. 13 C ssNMR, dynamic light scattering, and transmission electron microscopy show that, while native EPS has rigid molecular characteristics and contains small, loosely packed polysaccharide assemblies, lyophilized and resuspended EPS is disordered and contains larger dense aggregates, suggesting that structural water molecules in the interior of the polysaccharide assemblies are removed during extensive lyophilization. Importantly, mAbs to C. neoformans polysaccharide bind native EPS more strongly than lyophilized EPS. Together, these observations argue for caution when interpreting the biological and immunological attributes of polysaccharides that have been lyophilized to dryness. Graphical abstract: Unlabelled Image